Additive‐Assisted Novel Dual‐Salt Electrolyte Addresses Wide Temperature Operation of Lithium–Metal Batteries. Issue 16 (8th March 2019) - Shangguan, Xuehui; Xu, Gaojie; Cui, Zili; Wang, Qinglei; Du, Xiaofan; Chen, Kai; Huang, Suqi; Jia, Guofeng; Li, Faqiang; Wang, Xiao; Lu, Di; Dong, Shanmu; et al.
Abstract: In this study, self‐synthesized lithium trifluoro(perfluoro‐ tert ‐butyloxyl)borate (LiTFPFB) is combined with lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to formulate a novel 1m dual‐salt electrolyte, which contains lithium difluorophosphate (LiPO2 F2 ) additive and dominant carbonate solvents with low melting point and high boiling point. The addition of LiPO2 F2 into this novel dual‐salt electrolyte dramatically improves cycleability and rate capability of a LiNi0.5 Mn0.3 Co0.2 O2 /Li (NMC/Li) battery, ranging from −40 to 90 °C. The NMC/Li batteries adopt a Li–metal anode with low thickness of 100 µm (even 50 µm) and a moderately high cathode mass loading level of 10 mg cm −2 . For the first time, this paper provides valuable perspectives for developing practical lithium–metal batteries over a wide temperature range. Abstract : The addition of lithium difluorophosphate (LiPO2 F2 ) additive into a novel dual‐salt electrolyte dramatically improves cycleability and rate capability of a LiNi0.5 Mn0.3 Co0.2 O2 /Li (NMC/Li) battery, ranging from −40 to 90 °C. In this novel dual‐salt electrolyte, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and self‐synthesized lithium trifluoro(perfluoro‐ tert ‐butyloxyl)borate (LiTFPFB) are dissolved in dominant carbonate solvents with low melting point and high boiling point.